2018
DOI: 10.1074/jbc.ra118.004587
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions connecting the function of the serine-arginine–rich protein SRSF1 to protein phosphatase 1

Abstract: Splicing generates many mRNA strands from a single precursor mRNA, expanding the proteome and enhancing intracellular diversity. Both initial assembly and activation of the spliceosome require an essential family of splicing factors called serine-arginine (SR) proteins. Protein phosphatase 1 (PP1) regulates the SR proteins by controlling phosphorylation of a C-terminal arginine-serine-rich (RS) domain. These modifications are vital for the subcellular localization and mRNA splicing function of the SR protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…However, a much larger fraction of SA mutant is trapped in the cytosol despite NLS tagging. Consistent with prior work 31,32 , this finding suggests that RS phosphorylation is a major requirement for entry into the nucleus.…”
Section: Resultssupporting
confidence: 90%
“…However, a much larger fraction of SA mutant is trapped in the cytosol despite NLS tagging. Consistent with prior work 31,32 , this finding suggests that RS phosphorylation is a major requirement for entry into the nucleus.…”
Section: Resultssupporting
confidence: 90%
“…To accomplish this, we used a form of SRSF1 that is defective in entering the nucleus because of mutations in its NLS. In a previous study, we demonstrated that replacing 8 serines in the N terminus of the RS domain generates a mutant SRSF1 (GFP-SRSF1 mut ) resistant to SRPK1-dependent nuclear transport (29) (Fig. 5A).…”
Section: Nuclear Localization Of Clk1 Nls In Srsf1 Drives Clk1 Into Tmentioning
confidence: 85%
“…We next wished to determine whether mutation of the CLK1 binding residues impacts the phosphorylation state of SRSF1 by observing the migration of GFP‐SRSF1 on 10% SDS/PAGE. We showed previously that Ser‐Pro phosphorylation (hyper‐phosphorylation) can be monitored by reduced migration of GFP‐SRSF1 on low percentage SDS/PAGE [21,32]. We found that the ratio of slow‐migrating species compared to fast‐migrating species was much greater with HA‐SRPK1 than HA‐SRPK1 mut expression suggesting that the binding surface induces enhanced hyper‐phosphorylation in GFP‐SRSF1 (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…(D) Phosphorylation of SRSF1 by CLK1 with and without SRPK1 under steady-state conditions. CLK1 (250 nM), 32…”
Section: Activation Of Clk1 Requires the Clk1 Binding Site In Srpk1mentioning
confidence: 99%